PRINSIP PENDIDIKAN NILAI TAFSIR AL-AZHAR - H, Ahmad Syarif (Jurnal al Hikmah, 2017)
Education of values born as a tool for balancing the three domains of education, cognitive, psychomotoric and affective attempts to give an answer to the negative stigma of society which assumes that todays education system has failed to assume the role of instrument to mature human beings. With the constructions of value education, it is expected to be born human beings who are not only superior in the field of intellectual, but also excel in the realm of emotional and spiritual. The Quran as the main source of Islamic teachings, is believed by its adherents to have a life guide that is appropriate for every place and time where it is located. It is like a warehouse in which pearls and gems are stored. But not everyone can enter the warehouse. One of the nations best sons, Hamka, has tried to enter the warehouse and the result gave birth to a monumental work of al-Azhar commentary. It is through this book that we will see how Hamka values education principles.Using the thematic interpretation approach of al-Azhar interpretation, it is found that the principles of values education contained in Tafsir al-Azhar can be seen in three main themes, namely the meaning and purpose of education, the way human beings get value, and the method of delivering value. The meaning and purpose of values education according to Hamka is an effort made by learners to help learners in order to become a human being purnawan, meaning that humans who not only excel intellectually but also moral. To achieve that goal, man through the mind or the five senses and his heart or feelings already have great capital to do so. To obtain these values, values must be submitted. The way of delivering these values according to hamka is through an inculcation approach with storytelling methods and gives an idea of the positive and negative effects of those values (positive and negative reinforcement)